External Reserves and Macroeconomic Stability: Evidence from Sub-Saharan African Countries - Falmata Baba Abba; Yagana Alhaji Baba; Amina Ahmed Idris (Walidem Institute and Publishing, 2024)
This study investigates the effect of foreign exchange reserves accumulation on macroeconomic stability proxied by inflation, unemployment, exports, and GDP for a sample of 49 Sub-Saharan African countries from 2009 to 2021 using a panel (longitudinal) fixed model. Findings from this study reveal that foreign exchange reserves have a significant negative effect on unemployment and inflation; however, it shows a significant positive effect on exports, while gross domestic product (GDP) shows no significant relationship with foreign exchange reserves. To improve the overall economy of the listed sub-Saharan countries, the paper, therefore, recommends that sub-Saharan African countries adopt a mixture of investment-friendly and unemployment reduction policies by reinvesting investible surplus into inflationary controllable and productivity-boosting policies that will stimulate economic growth rather than keeping this huge amount of resources redundant. The study adopted a qualitative research methodology where the study uses panel data, the data is secondary and is sourced from the World Bank Development Indicators.